Responses of the maize rhizosphere soil environment to drought-flood abrupt alternation stress - Gao, Yun; Zhao, Yulong; Li, Ping; Qi, Xuebin (Frontiers in Microbiology, 2023)
Changes in the soil environment in the root zone will affect the growth, development and resistance of plants. The mechanism underlying the effect of drought and flood stress on rhizosphere bacterial diversity, soil metabolites and soil enzyme activity is not clear and needs further study. To analyse the dynamic changes in bacteria, metabolites and enzyme activities in the rhizosphere soil of maize under different drought-flood abrupt alternation (DFAA) stresses, the barrel test method was used to set up the 'sporadic light rain' to flooding (referring to trace rainfall to heavy rain) (DFAA1) group, 'continuous drought' to flooding (DFAA2) group and normal irrigation (CK) group from the jointing to the tassel flowering stage of maize. The results showed that Actinobacteria was the most dominant phylum in the two DFAA groups during the drought period and the rewatering period, and Proteobacteria was the most dominant phylum during the flooding period and the harvest period. The alpha diversity index of rhizosphere bacteria in the DFAA2 group during the flooding period was significantly lower than that in other stages, and the relative abundance of Chloroflexi was higher. The correlation analysis between the differential genera and soil metabolites of the two DFAA groups showed that the relative abundance of Paenibacillus in the DFAA1 group was higher during the drought period, and it was significantly positively correlated with the bioactive lipid metabolites.The differential SJA-15 bacterium was enriched in the DFAA2 group during the flooding period and were strongly correlated with biogenic amine metabolites. The relative abundances of Arthrobacter, Alphaproteobacteria and Brevibacillus in the DFAA2 group were higher compared with DFAA1 group from rewatering to harvest and were significantly positively correlated with hydrocarbon compounds and steroid hormone metabolites. The acid phosphatase activity of the DFAA1 group was significantly higher than that of the DFAA2 group during the flooding period. The study suggests that there is a yield compensation phenomenon in the conversion of 'continuous drought' to flooding compared with 'sporadic light rain', which is related to the improvement in the flooding tolerance of maize by the dominant bacteria Chloroflexi, bacterium SJA-15 and biogenic amine metabolites.